2018
DOI: 10.3102/0034654318794134
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research Connecting Digital Storytelling, Photovoice, and Civic Engagement

Abstract: The purpose of this review is to expand understanding of the ways culturally, ethnically, and racially diverse youth have begun to reimagine urban and rural spaces using digital storytelling and photovoice, two methods that often fall under the broad field of youth participatory action research. To explain the conditions under which these methods favor movement toward socially just ideas and actions, we also build on and extend research in critical youth empowerment to call attention to the relational nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 84 publications
(112 reference statements)
0
45
0
5
Order By: Relevance
“…It was initially TSANG 138 beijing international review of education 2 (2020) 136-152 Carlson, Engebretson, & Chamberlain, 2006). In other words, the critical approach considers photovoice as a strategy to empower participants and bring about social change (Greene et al, 2018). For example, C. C. Wang's (1999) study showed how photovoice can be used as an intervention strategy to empower women to improve their health in rural China.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially TSANG 138 beijing international review of education 2 (2020) 136-152 Carlson, Engebretson, & Chamberlain, 2006). In other words, the critical approach considers photovoice as a strategy to empower participants and bring about social change (Greene et al, 2018). For example, C. C. Wang's (1999) study showed how photovoice can be used as an intervention strategy to empower women to improve their health in rural China.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing interest in what has been termed "the affective turn" in social sciences (Clough, 2008;Zembylas, 2014), the issues of emotion, feeling, and embodiment have come increasingly to the fore, including in the field of qualitative health research (Cromby, 2011(Cromby, , 2012a(Cromby, , 2012bLyons & Chamberlain, 2012). Limitations of space preclude us from commenting in detail on this large movement, but relevant to this article is the fact that some researchers have argued that accessing emotion in research is difficult, but possibly eased through the use of methods other than traditional talkand-text methods (Baumann, Merante, et al, 2020;Cromby, 2012a;Greene et al, 2018;McGrath et al, 2020). Although there may be something intuitively correct about the claim that methods such as photo-elicitation (Edmondson et al, 2018), for example, may provide easier access to emotion than more traditional methods, there is little systematic research on the various contributions of different methods and media to understanding emotion in health and illness.…”
Section: The Affective Turn In Qualitative Researchmentioning
confidence: 99%
“…The sustained growth and versatility of arts-based approaches to research and the ever-expanding prominence of qualitative methods makes this an exciting time to be a qualitative health researcher. Qualitative methods have a long-standing and well-established place in health research, and the expansion in the range of qualitative methods has seen increasing use of approaches to data collection which rely on more than just text-and-talk, including photovoice (Aparicio et al, 2020; Greene et al, 2018; Han & Oliffe, 2016; Hunt et al, 2018; Macdonald et al, 2019; Watchman et al, 2020), digital and other forms of storytelling (Bulk et al, 2020; de Jager et al, 2017; Douglas & Carless, 2018; Greene et al, 2018; Moreau et al, 2018; Tatano Beck, 2020), walking methodologies (Springgay & Truman, 2017), video methods (Baumann, Lhaki, & Burke, 2020; Hansen, 2018), theater methods (Bleuer et al, 2018; Erel et al, 2017; Parent et al, 2017; Torrissen & Stickley, 2018), and a range of other arts-based methods (Candy & Edmonds, 2017; Chamberlain et al, 2018; Coemans & Hannes, 2017; Hammond et al, 2018; Wolf, 2011). A recent review of arts-based methods with vulnerable populations (Coemans & Hannes, 2017) shows that researchers in this field are using an array of media across different arts modalities, although photographic-based methods dominate in the field, with theater-based methods a distant second.…”
mentioning
confidence: 99%
“…Photovoice is often argued to be a reflexive and inclusive method that allows for differing viewpoints. Variations of this methodology have been used to reimage urban spaces for culturally, ethnically, and racially diverse youth (Greene et al, 2018); provide unique opportunities for constructing narratives for ethnic minorities (Colón-Ramos et al, 2018); increase gender inclusivity (Yoshihama & Yunomae, 2018); and construct and express individual resilience outside the more common western-centric discourse (Pearce et al, 2017).…”
Section: Photovoice Tourism and Disastermentioning
confidence: 99%